Il "trompe-l'œil" letterario, ovvero il sorriso ironico nell'opera di Wilhelm Hauff - Acciaioli, Stefania (Premio Tesi di Dottorato, 2012)
Literary trompe-l'oeil intends to emancipate the enigmatic and distinctive figure of Hauff from his long and unjust marginalization resulting from a now outdated current of criticism, to offer a new interpretation of his Märchen for a general rereading of this modern literary caricaturist's works. On approaching his texts, one cannot but notice how they are imbued with continual and insistent, bewitching, caustic and alienating allusions, just like the Mona Lisa's smile. With a constant critical scepticism and a subtle illusionist skill, this demythologized 'budding Satan' looks at the present situation through the 'diabolic lenses' of irony, making his works a sort of literary Befreiungskrieg, in which he lays claim to a heterotopic space of free fantastic-humorist expression, along the undulating route leading from Sterne to Heine via Jean Paul.